The Impact of Digital Media Use on Muslim Entrepreneurs' Intention to Apply for Halal Certificate: Empirical Evidence from Indonesia - Ridlwan, Ahmad Ajib; Timur, Yan Putra; Ryandono, Muhammad Nafik Hadi; Takidah, Erika; Abdul Aziz, Azreen Hamiza; Juniarti, Rosa Prafitri (Indonesian Journal of Halal Research, 2025)
The Indonesian government is striving to encourage Muslim entrepreneurs to obtain halal certification for all products produced, imported, and sold within Indonesia. Digital media has emerged as a viable solution to enhance the convenience and practicality of Muslim entrepreneurs in applying for halal certification. This study aims to examine factors that influence Muslim entrepreneurs' halal certification applications through digital media, using the DeLone and McLean and the Unified Theory of Acceptance and Use of Technology (UTAUT) models. This quantitative study analyses 350 Indonesian Muslim entrepreneurs using partial least square structural equation modeling (PLS-SEM). Researchers obtain data using non-probability sampling approaches. The results of the study indicate that the constructs of performance expectancy (PE), effort expectancy (EE), social influence (SI), and service quality (SEQ) have a positive and significant effect on intention (INT). In addition, the facilitating condition (FC) has a positive influence on INT but is not significant. While the constructs of system quality (SYQ) and information quality (IQ) have a positive and significant effect on user satisfaction (US), the correlation of the two constructs to INT is not significant. Therefore, it can be concluded that PE, EE, and SI are the key driving factors for Muslim entrepreneurs in using digital media to apply for halal certification. According to the results, developing user-friendly features and technology systems is highly recommended. Pre- and post-submission service quality must be improved. Therefore, halal process assistance officers (PPH) are proposed to support Indonesian Muslim entrepreneurs.